2019
DOI: 10.1155/2019/5720290
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Two-Stop-Line Signalized Roundabout: Capacity and Optimal Cycle Length

Abstract: Two-stop-line signalized roundabouts (TSLSR) are widely utilized in China. To calculate the capacity and optimal cycle length accurately, a model considering internal space constraint of the roundabout is developed in this paper. Firstly, the operational principle of TSLSR is analyzed. TSLSR is modeled as being equivalent to a four-phase intersection with left-turn protection phases, and the left-turn lane is further simplified as the “short-lane model”. Secondly, based on the above analysis, the capacity of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Concerning signal timing studies, several researchers tried to enhance roundabout capacity by applying a signal timing plan and adjusting the phase sequence [24][25][26][27][28][29][30]. In [24,25], direct and full control method was tested and a two-stop line roundabout was proposed to help left-turning vehicles.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning signal timing studies, several researchers tried to enhance roundabout capacity by applying a signal timing plan and adjusting the phase sequence [24][25][26][27][28][29][30]. In [24,25], direct and full control method was tested and a two-stop line roundabout was proposed to help left-turning vehicles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning signal timing studies, several researchers tried to enhance roundabout capacity by applying a signal timing plan and adjusting the phase sequence [24][25][26][27][28][29][30]. In [24,25], direct and full control method was tested and a two-stop line roundabout was proposed to help left-turning vehicles. The research calculated the best green time for straight traffic on each approach at the first stop line and vehicles turning left on the circulating lanes at the second stop line [25].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study findings suggested that cycle length between 60s and 90s is suitable for a 2-lane roundabout that uses the TSLSR phasing plan method. In addition, Jiang et al (2019) [12] found that the cycle length and radius of the central island affected the capacity of signalised roundabout using the TSLSR phasing plan. Thus, the selection of optimum cycle time for TSLSR should be carefully examined to avoid undesired results.…”
Section: Fig 1 -Sample Of a Signalized Roundabout Geometry [6]mentioning
confidence: 99%
“…Jiang ve diğ., yapmış oldukları çalışmada, sinyalize dönel kavşağın kapasitesini maksimize eden en uygun devre süresini belirlemeyi amaçlamışlardır. Sonuç olarak, çalışma kapsamında geliştirilen model ile kavşak kapasitesinin önemli oranda arttırılabileceği görülmüştür [18].…”
Section: Introductionunclassified